Diet and its composition of the proboscis monkey (Nasalis larvatus Wurmb) in rubber forest of Tabalong District, South Kalimantan - MOCHAMAD ARIEF SOENDJOTO; HADI SUKADI ALIKODRA; MUHAMMAD BISMARK; HERU SETIJANTO (Society for Indonesian Biodiversity, 2006)
Diet of the proboscis monkey (Nasalis larvatus Wurmb) inhabiting rubber forests was poorly known. The research objectives were to identify plants or other organisms which functions as food sources, estimate the amount of food a day, and determine the content of food nutrition. Identification of food sources and estimation of the amount of food were conducted in the field, but the nutrition content was analyzed in the laboratory. Eighteen plant species belonging to at least ten families were found as food sources. The monkey was likely to be folivore. Based on IARF (individual activity records of feeding) method, most of food was consisted of leaves (80.9%) and others were flowers (11.3%), fruits (6.77%), and barks (0.95%). The monkey also fed grasshoppers and termites, although few occasions were found. However, the number of food plant species and the percentage of food composition could change, because on some locations, out of the research location, we found and also people reported other plant species consumed by the proboscis monkey. By sampling the feeding rate on leaves of three species, the amount of food ranged 919.96-1537.59 g wet weight or 168.57-515.94 g dry weight. In addition, those sampled leaves contained nutrition and essential minerals that were required by this colobine monkey. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKeywords: proboscis monkey, food, nutrition, rubber forest.